2001
DOI: 10.1016/s0002-9440(10)64676-7
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Endothelial Cell Proliferation and Microvascular Remodeling in Chronic Inflammation

Abstract: Angiogenesis and vascular remodeling are features of many chronic inflammatory diseases. When diseases evolve slowly, the accompanying changes in the microvasculature would seem to be similarly gradual. Here we report that the rate of endothelial cell proliferation and the size of blood vessels increases rapidly after the onset of an infection that leads to chronic inflammatory airway disease. In C3H mice inoculated with Mycoplasma pulmonis, the tracheal microvasculature, made visible by perfusion of Lycopersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
115
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 40 publications
10
115
0
Order By: Relevance
“…To confirm that the dextran injection method could precisely mark blood vessels in tumors, we did a coinjection experiment with the Texas red-conjugated dextran and FITC-conjugated LEL, which specifically binds to endothelial cells (19). Using confocal microscopy, we observed that the majority of dextran-marked channels in the tumors were colocalized with FITC-LEL staining ( Fig.…”
Section: Resultsmentioning
confidence: 82%
“…To confirm that the dextran injection method could precisely mark blood vessels in tumors, we did a coinjection experiment with the Texas red-conjugated dextran and FITC-conjugated LEL, which specifically binds to endothelial cells (19). Using confocal microscopy, we observed that the majority of dextran-marked channels in the tumors were colocalized with FITC-LEL staining ( Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Lectin staining was performed as described in ref. 20. Immunostaining was performed with anti-CD31 (MEC13.3, Pharmingen) and anti-SMC-␣-actin (anti-␣-SMA) (1A4-AP, Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, frozen sections were digested with 0.005% pepsin (Sigma, St. Louis, Missouri) in 0.01 HCl for 30 min at 37 °C followed by treatment with 4 N HCl for 30 min at room temperature. Sections were then blocked by incubation in 5% goat serum in PBS for 30 min [43] prior to incubation with antibody. Fluorescence microscopic imaging of endothelial (CD31 + CD105 + flk1) [38,39], pericyte (NG2 or PDGF β-receptor) [13,18,19], and nuclear (BrdU) markers [43] was performed according to the published methods.…”
Section: Tissue Processing Immunohistochemistry and Imagingmentioning
confidence: 99%